The analysis of the range of antipsoriatic medicines used in the local treatment of mild psoriasis in Ukraine: uk. - Nemchenko, A. S.; Taranenko, Yu.S.; Gladukh, Ie. V.; Mishchenko, V. I. (Social Pharmacy in Health Care, 2021)
Today, according to various authors, the prevalence of psoriasis is 12-15% of the total number of skin diseases. The incidence of psoriasis in countries with high economic development is 1.5-2%. Therefore, the development of new drugs for the treatment of psoriasis is an urgent problem of domestic pharmacy. Aim. To analyze the range of antipsoriatic drugs used in the local treatment of mild psoriasis in Ukraine. Materials and methods. The assortment of drugs was analyzed in accordance with the State Registry of Medicines of Ukraine and the АТС classification system. In the course of the research, the content analysis and the analysis of scientific information using internet sources on the selected topic were performed; analytical and statistical methods of analysis were applied. Results. According to the retrospective analysis, there is a constant change in the ratio of domestic and foreign producers during the study period. It has been determined that 17.5 % are occupied by semisolid dosage forms; cream (10.0 %), paste (5.0 %) and gel (2.5 %) are the closest in the form to the drug proposed for introduction. The analysis of dermatological drugs compared to the analogs has allowed us to determine that there are 8 trade names at the domestic pharmaceutical market. Among them, 75.0 % have a synthetic component, while 25.0 % are combined preparations (herbal components and synthetic composition) Conclusions. The range of antipsoriatic drugs in the local treatment of mild psoriasis has been analyzed in the article. In recent years, the research on the treatment of this disease has been actively conducted due to the large number of patients. There is a need to develop new effective domestic anti-psoriatic drugs. It is advisable to carry out further development of new drugs of the combined composition for the treatment of mild psoriasis. Key words: antipsoriatic medicines; assortment analysis; forms of psoriasis; local treatment.